Respuesta :
in the equation you have to replace all x's with -1
f (-1) = (-1)^2 - 8(-1) +5
f (-1) = 1 + 8 + 5
f (-1) = 14
the f(-1) stand for the function of -1. it is also equivalent to y
f (-1) = (-1)^2 - 8(-1) +5
f (-1) = 1 + 8 + 5
f (-1) = 14
the f(-1) stand for the function of -1. it is also equivalent to y
Answer:
f(-1)=14
Step-by-step explanation:
Given : Function - [tex]f(x)=x^2-8x+5[/tex]
To find : The value of f(-1)
Solution : Follow the steps :
Step 1- Write the function
[tex]f(x)=x^2-8x+5[/tex]
Step 2- Put x=-1 to find the value of f(-1)
[tex]f(-1)=(-1)^2-8(-1)+5[/tex]
Step 3- Solve the above equation
[tex]f(-1)=1+8+5[/tex]
[tex]f(-1)=14[/tex]
Therefore, f(-1)=14